Perancangan Sistem Inventory Untuk Stok Barang Herbisida Pada UD. Anugrah Jaya Tani Dengan Bahasa Pemrograman PHP dan Database MySql - Amelia Sari Lubis, Fitri; Sahara Lubis, Siti; Hendrik, Billy (Jurnal Sains Informatika Terapan, 2023)
Advances in information and communication technology are growing rapidly in all directions so that a lot of information is produced from technology and is applied in various fields. In the field of information technology, an inventory system is also needed which is used to view the stock of goods at UD. Anugrah Jaya Tani. UD. Anugrah Jaya Tani is a kiosk that sells various herbicides. The use of chemical herbicides is intended so that they do not affect cultivated plants but affect the growth of weeds. Therefore, it takes herbicides or substances that are selective and precise in controlling weeds. Inventory systems are one of the parts that can also be developed with the existence of internet resources. The internet can play a role in facilitating activities. This is because inventory activities require communication between the parties involved in this matter. The purpose of using an inventory system where the most basic is being able to align customer demand with existing supply or control existing inventory. The results of this study are to determine the amount of stock of goods to be marketed, create a system that can be accessed by anyone, and create an attractive consultation layout. Inventory is storage owned by a company to be traded or used for company operations. All items are referred to as an inventory system, depending on the type of the Company's business